2023
DOI: 10.3389/fcimb.2023.1251309
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in carbon dots for anti-pathogen applications in oral cavity

Yuying Jiang,
Chuqiang Yin,
Jianning Mo
et al.

Abstract: BackgroundOral microbial infections are one of the most common diseases. Their progress not only results in the irreversible destruction of teeth and other oral tissues but also closely links to oral cancers and systemic diseases. However, traditional treatment against oral infections by antibiotics is not effective enough due to microbial resistance and drug blocking by oral biofilms, along with the passive dilution of the drug on the infection site in the oral environment.Aim of reviewBesides the traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 191 publications
0
1
0
Order By: Relevance
“…It has been confirmed that biofilm formation is a cooperative group behavior in which bacterial populations live embedded in a self-generated polymer extracellular matrix. This process is considered one of the most common cooperative behaviors exhibited by bacteria (Brao et al, 2021;Gao et al, 2023;Jiang et al, 2023;Liu et al, 2023). The biofilm primarily consists of sessile cell populations derived from microorganisms and quorum-sensing systems that serve as a cell-cell communication mechanism (Tsang et al, 2018).…”
Section: Definition Formation and Characteristics Of Biofilmmentioning
confidence: 99%
“…It has been confirmed that biofilm formation is a cooperative group behavior in which bacterial populations live embedded in a self-generated polymer extracellular matrix. This process is considered one of the most common cooperative behaviors exhibited by bacteria (Brao et al, 2021;Gao et al, 2023;Jiang et al, 2023;Liu et al, 2023). The biofilm primarily consists of sessile cell populations derived from microorganisms and quorum-sensing systems that serve as a cell-cell communication mechanism (Tsang et al, 2018).…”
Section: Definition Formation and Characteristics Of Biofilmmentioning
confidence: 99%